Penerapan Employer Branding dan Employee Value Proposition Untuk Menciptakan Employee Engagement dalam Perspektif Bisnis Islam - Fatih Fuadi; Destin Fitria Anjayani (MAMEN: Jurnal Manajemen, 2023)
PT Colombus Bandar Lampung, one of the companies operating in the world of buying and selling cash and credit for electronics and furniture, has the problem that every year from 2020 to 2022, the turnover value exceeds 10%. If the annual turnover rate in a company exceeds 10%, it can be categorized as high. One way that can be done to retain existing workers is to always create internal offers that can increase employee loyalty. This research aims to determine the application of employer branding, the application of employee value proportion, the impact of the application of employer branding and employee value proportion on employee engagement, and the application of employer branding and employee value proposition strategies to create employee engagement from an Islamic business management perspective. This research uses a qualitative approach. PT Colombus has a friendly work environment, which creates a feeling of comfort. Employees felt a friendly work environment and continuous improvement when PT Colombus formulated employee value proportions